Two-Week Burden of Arrhythmias across CKD Severity in a Large Community-Based Cohort: The ARIC Study - Kim, Esther D. (J Am Soc Nephrol, 2021)
BACKGROUND: CKD is associated with sudden cardiac death and atrial fibrillation (AF). However, other types of arrhythmia and different measures of the burden of arrhythmias, such as presence and frequency, have not been well characterized in CKD. METHODS: To quantify the burden of arrhythmias across CKD severity in 2257 community-dwelling adults aged 71–94 years, we examined associations of major arrhythmias with CKD measures (eGFR and albuminuria) among individuals in the Atherosclerosis Risk in Communities study. Participants underwent 2 weeks of noninvasive, single-lead electrocardiogram monitoring. We examined types of arrhythmia burden: presence and frequency of arrhythmias and percent time in arrhythmias. RESULTS: Of major arrhythmias, there was a higher prevalence of AF and nonsustained ventricular tachycardia among those with more severe CKD, followed by long pause (>30 seconds) and atrioventricular block. Nonsustained ventricular tachycardia was the most frequent major arrhythmia (with 4.2 episodes per person-month). Most participants had ventricular ectopy, supraventricular tachycardia, and supraventricular ectopy. Albuminuria consistently associated with higher AF prevalence and percent time in AF, and higher prevalence of nonsustained ventricular tachycardia. When other types of arrhythmic burden were examined, lower eGFR was associated with a lower frequency of atrioventricular block. Although CKD measures were not strongly associated with minor arrhythmias, higher albuminuria was associated with a higher frequency of ventricular ectopy. CONCLUSIONS: CKD, especially as measured by albuminuria, is associated with a higher burden of AF and nonsustained ventricular tachycardia. Additionally, eGFR is associated with less frequent atrioventricular block, whereas albuminuria is associated with more frequent ventricular ectopy. Use of a novel, 2-week monitoring approach demonstrated a broader range of arrhythmias associated with CKD than previously reported.